Strategies of In Situ Generated Magnesium Catalysis in Asymmetric Reactions - Wang, Linqing; Yang, Dongxu (Synlett, 2021)
Magnesium (Mg) is a cheap, non-toxic, and recyclable alkaline earth metal that constitutes about 2% weight in the Earth’s crust. The use of magnesium catalysts to forge chiral moieties in molecules is highly attractive. Based on our work in recent years, we describe the current progress in the development of in situ generated magnesium catalysts and their application in asymmetric synthesis. In this perspective, a critically concise classification of in situ generated magnesium catalytic modes, with relevant examples, is presented, and representative mechanisms of each category are discussed. Building on the established diverse strategies, one can foresee that more innovative and structurally creative magnesium catalysts that are generated in situ will be developed to overcome more formidable challenges of catalytic enantioselective reactions.1 Introduction2 Magnesium Catalysts Generated in Situ from Chiral Ligands Containing Dual Reactive Hydrogens3 Magnesium Catalysts Generated in Situ from Monoanionic Chiral Ligands4 Bimetallic and Polymetallic Magnesium Catalysts Assembled in Situ5 Summary and Outlook
Keywords: magnesium; in situ assembly; asymmetric synthesis; catalytic strategies; chiral ligand